PENGARUH FRAUD DIAMOND THEORY TERHADAP KECURANGAN (FRAUD) PADA KOPERASI KREDIT PINTU AIR - Paulus Libu Lamawitak; Emilianus Eo Kutu Goo (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2021)
This study aims to determine the effect of partial financial target, ineffective monitoring, and capability for fraud. The data of this study were obtained from questionnaires. This research includes quantitatives research. The population of this study is 100 employees who work at the Sluice Credit Cooperative and the sample determination technique uses the slovin formula. The number of respondents in this study were 50 employees. The instrument reliability test includes the validity and reliability test, the classic assumption test includes the normality test, the heterokedasticity test and the multicollinearity test. Data analysis techniques using multiple linear regression analysis with hypothesis testing (t test). The results showed that the (1) financial target had a significant effect on fraud with a significant value of 0,003 < 0,05 (2) ineffective monitoring has a significant effect on fraud with a significant value of 0,002 < 0,05; (3) capability has a significant effect on fraud with a significance value of 0,000 < 0,005.